150k views
14 votes

6(x-1)-x=-21


\tt Thanks! :)

User Cira
by
5.7k points

2 Answers

7 votes
x = -3

Solution:
Distribute
6(x)+(6)(-1)+-x=-21

Combine
(6x+-x) + (-6) = -21
5x + -6 = -21
5x - 6 = -21

Add 6 to both sides
5x -6 + 6 = -21 +6
5x = -15

Divide both sides by 5
5x/5 = -15/5
x = -3
User Matthew Brown
by
5.1k points
6 votes

Explanation:

Given that:

6(x - 1) - x = -21

Multiply the number outside of the brackets with numbers in the brackets on LHS.

⇛6x - 6 - x = -21

Shift constant from LHS to RHS, changing it's sign.

⇛6x - x = -21 + 6

Subtract the values on LHS and RHS.

⇛5x = -15

Shift the number 5 from LHS to RHS.

⇛x = -15/5

Therefore x = -3

Please let me know if you have any other questions.

User Bandana
by
5.3k points